Nonalcoholic fatty liver disease and obesity - Salgado Júnior,Wilson (2006)
PURPOSE: The aim of this review is to update concepts of the nonalcoholic fatty liver disease (NAFLD) and to establish a relationship between this condition and obesity. METHODS: By means of a comprehensive literature review where special attention was devoted to articles published in the last 5 years, NAFLD is discussed in view of new concepts, diagnosis, staging, and treatment. RESULTS: NAFLD is emerging as one of the main causes of chronic liver disease and it is believed to be the hepatic component of the metabolic syndrome, whose central features include obesity, hyperinsulinemia, peripheral insulin resistance, diabetes, dyslipidemia, and hypertension. The surgical treatment of morbid obesity is one of the options available for the treatment of NAFLD. CONCLUSION: Nonalcoholic fatty liver disease is strongly related with obesity.